Organizational Culture as a Mediator Between Knowledge Management and Performance in Nepal’s Private Banks - Bhusal, Bharat (Kshitiz Management Review, 2025)
This study examines how organizational culture mediates the link between knowledge management (KM) practices and organizational performance in Nepalese private banks. Using structural equation modeling (SEM) and data from 440 respondents from 11 private banks, the mediating effect of organizational culture on the relationship between four KM dimensions—knowledge acquisition, conversion, transfer, and application—and bank performance has been assessed. The results reveal that knowledge acquisition and transfer directly enhance performance. Knowledge application significantly outlines organizational culture, whereas conversion negatively influences culture but positively impacts performance. Mediation analysis shows complementary mediation for application, competitive mediation for conversion, and direct-only non-mediation for acquisition. In particular, the transfer’s influence on performance is direct. These results emphasize the indicated roles of different knowledge processes and their relations with organizational culture in inspiring bank performance. These findings highlight the comprehensive role of organizational culture in understanding KM practices for better performance, suggesting that effective implementation needs a culture-sensitive approach.